We Are not All: Building an exhibition, empathy and memory to address pain (Cadernos de Sociomuseologia, 2022)
The violent murders of women due to their gender, also known as feminicides, continue to increase and have become more commonplace in Mexico, which ranks as one of the most dangerous countries to be a woman in. The increase in crimes and the impunity surrounding them has created a culture of indignation in various sectors of society and has led many to mobilize. An example of these actions are those proposed by No Estamos Todas, who through illustration and digital media attempt to bring visibility to extreme violence against women. This dissertation seeks to investigate the concept of feminicide, its origins and classifications, and analyzes many diverse projects and worldwide proposals that document, inform, and bring awareness to the issue of gender-based violence. In a second phase, based on the premise that museums have social functions and should be active in the promotion of human rights and gender equality, the creation of a museological exhibition of graphic and multimedia content based on the work of No Estamos Todas was proposed and took place in November 2019 in the city of Lisbon.Keywords: Human rights, gender equality, sociomuseology, expography, exhibition.